Evaluating the Adoption and Impact of Systematic Compost Production: Evidence from a Survey in Northern Bangladesh - Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
This study evaluates the adoption, feasibility, and socio-economic impacts of systematic composting among 100 households in Northern Bangladesh as part of a CGIAR initiative on mixed farming systems and sustainable farming. Farmers received support and training for two to three years from the projects, followed by a survey to assess the benefits and challenges of systematic compost production in their homesteads. All surveyed households were knowledgeable about compost production and had received training, primarily from IRRI (84%). In compost production, 100% of households use cow dung, followed by kitchen waste (46%), poultry manure (24%), and crop residues (12%). On average, households complete 2.87 compost cycles per year, producing around 3,000 kg annually. Compost is mainly used on vegetables and crop fields (87%), while 13% of households sell it, generating supplementary income averaging BDT 2,100 per year. Compost usage varies by season, peaking during the Rabi season, with 88% of households utilizing it for various crops such as rice, potatoes, mustard, vegetables, and maize. Farmers report clear benefits: improved soil fertility (97%) and higher crop yields (86%), with 86% considering compost more effective than chemical fertilizers. Compost also reduces dependence on chemical inputs, contributing to sustainable farming practices. Farmers demonstrate strong commitment to compost production, with 66% planning to continue current levels and 34% intending to expand. Key support needs include training and technical advice (100%), financial assistance (36%), and market linkages (16%), emphasizing the importance of capacity-building to sustain and scale compost production. Overall, the results highlight compost as a vital component of crop productivity, soil health, and potential income diversification, reinforcing its role in promoting sustainable agriculture in the study area.